Business students' perspective of learning law education - Ambaras Khan, Hanna (Editorial Universidad de Almería, 2021)
Law education is a must subject in many courses due to its importance. However, law is perceived as a complicated subject and consumes much time, particularly for non-law students who do not aim to study law throughout their course registration. Indeed, law education is a dull topic since it is usually taught in a conventional style. School of Business and Economics, Universiti Putra Malaysia, has offered one law subject to the business students, "Business Law". It was realized that most of the students enrolled in that course faced difficulty in learning law education. This paper aims to study the business students' experience of learning law and propose effective teaching methods to ensure that legal topics are taught more acceptably. This paper adopts a qualitative method in collecting data where three surveys and two short interviews were conducted. It was found that the students have found this law subject complicated. Still, they liked the subject and agreed to learn it with some appropriate learning activities. Thus, something must be done to contest these views and change students' perspective on legal courses. This subject needs to be taught in a manner acceptable to attract the students' attention and interest. During the Covid-19 pandemic, all learning activities are conducted through the online platform. Therefore, the lecturer must have a good teaching plan to ensure that students can learn and enjoy law.